De Novo Transcriptome Assembly and Analysis of the Flat Oyster Pathogenic Protozoa Bonamia Ostreae - Chevignon, Germain; Dotto-Maurel, Aurélie; Serpin, Delphine; Chollet, Bruno; Arzul, Isabelle (Frontiers in Cellular and Infection Microbiology, 2022)
The flat oyster Ostrea edulis is an oyster species native to Europe. It has declined to functional extinction in many areas of the NE Atlantic since several decades. Factors explaining this decline include over exploitation of natural populations and diseases like bonamiosis, regulated at the EU and world scales and caused by the intracellular protozoan parasite Bonamia ostreae. To date very few sequences information is available for this Haplosporidian species. We present here the first transcriptome of B. ostreae. Because this protozoa is not yet cultivable, it remains extremely challenging to obtain high quality -omic data. Thanks to a specific parasite isolation protocol and a dedicated bioinformatic pipeline we were able to obtain a high-quality transcriptome for an intracellular marine micro-eukaryote, which will be very helpful to better understand its biology and to consider the development of new relevant diagnostic tools.